2019
DOI: 10.1097/bpb.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

An alternative to plaster cast treatment in a pediatric trauma center using the CAD/CAM technology to manufacture customized three-dimensional-printed orthoses in a totally hospital context: a feasibility study

Abstract: The aim of this study is to implement the clinical use of the three-dimensional (3D) design and printing technology in pediatric pathologies requiring immobilization. We describe the manufacturing process of the 3D device in place of the plaster cast usually applied to a child 48/72 h after the access to the Trauma Center Traumatology Hub. This procedure had already been performed at Level II, Trauma Center, Campania Region, Orthopaedic Division of Santobono Children’s Hospital, Naples, Italy. The operative ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 24 publications
0
65
0
Order By: Relevance
“…One study published in 2019 evaluated the clinical use of 3D printing in pediatric fractures requiring immobilization. 8 Eighteen children wore their 3D devices in 12 to 24 h. The results of the study indicated that the use of a 3D device instead of a traditional plaster cast can be an effective treatment of pediatric nondisplaced metaphyseal distal radius fractures, with high overall patient satisfaction. 8 We believe that 3D technology could be extended to the treatment of more complex fractures in the future.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One study published in 2019 evaluated the clinical use of 3D printing in pediatric fractures requiring immobilization. 8 Eighteen children wore their 3D devices in 12 to 24 h. The results of the study indicated that the use of a 3D device instead of a traditional plaster cast can be an effective treatment of pediatric nondisplaced metaphyseal distal radius fractures, with high overall patient satisfaction. 8 We believe that 3D technology could be extended to the treatment of more complex fractures in the future.…”
Section: Discussionmentioning
confidence: 98%
“…8 Eighteen children wore their 3D devices in 12 to 24 h. The results of the study indicated that the use of a 3D device instead of a traditional plaster cast can be an effective treatment of pediatric nondisplaced metaphyseal distal radius fractures, with high overall patient satisfaction. 8 We believe that 3D technology could be extended to the treatment of more complex fractures in the future. One systemic review published in 2019 introduced software systems that calculate the deformity parameters for external fixation to treat leg length discrepancies with concomitant angular and/or rotational deformities.…”
Section: Discussionmentioning
confidence: 98%
“…Patient satisfaction using plaster cast is poor [1] due to the physical characteristics of this old medical device. To overcome this drawback, the use of computeraided design (CAD) and 3D printing technology to produce personalized plastic casts, have been largely proposed [1][2][3][4][5] increasing the public awareness in the clinical use of these low cost and widely available technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the feasibility of the clinical use of orthopaedic personalized 3D printed cast for the treatment of forearm fractures in paediatric patients [5]. Thus, in daily clinical activities, it is necessary to implement a production phase compliant with time required by clinical course, less than 24/36 h from trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the clinical assessment of 3D-printed splints, two references were found that compare medical results of traditional vs 3D-printed splints (Chen et al , 2017; Guida et al , 2019). Other research studies, such as Li and Tanaka (2018a) and Paterson et al (2014) are focused on analyzing the feasibility of using dedicated CAD applications for the splint design process.…”
Section: Introductionmentioning
confidence: 99%